Investigation of Light Non-Aqueous Phase Liquid Migration Single and Double-Porosity Soil Using Light Transmission Visualization Method (LTV) - Alazaiza, M. Y. D.; Ngien, S. K.; Bob, M. M.; Kamaruddin, S. A.; Wan Faizal, Wan Ishak (EDP Sciences, 2016)
Two experiments were conducted to investigate the migration of light non-aqueous phase liquid (LNAPL) in two different porous media using LTV technique. The first media was fine sand as a single-porosity and the second media was S300 kaolin as a double-porosity. The two media were packed separately in the flow chamber and then LNAPL was injected from the top of the model and the migration of LNAPL (Toluene) was observed using a digital camera connected to a laptop and controlled using special software. The images were captured according to a predetermined time interval set by the software. The results show a significant difference in the migration of LNAPL in the two porous media, where the migration in the double-porosity media was much faster than the migration in the single-porosity. This finding is due to the occurrence of inter-aggregate pores in the double-porosity soil structure. This paper shows that more attention should be given towards the pollution of the groundwater sources that are located within or near the double-porosity media especially the agricultural soil.